2022
DOI: 10.3389/fbioe.2022.907538
|View full text |Cite
|
Sign up to set email alerts
|

Novel Designed Proteolytically Resistant VEGF-B186R127S Promotes Angiogenesis in Mouse Heart by Recruiting Endothelial Progenitor Cells

Abstract: Background: Previous studies have indicated that vascular endothelial growth factor B186 (VEGF-B186) supports coronary vascular growth in normal and ischemic myocardium. However, previous studies also indicated that induction of ventricular arrhythmias is a severe side effect preventing the use of VEGF-B186 in cardiac gene therapy, possibly mediated by binding to neuropilin 1 (NRP1). We have designed a novel VEGF-B186 variant, VEGF-B186R127S, which is resistant to proteolytic processing and unable to bind to N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Even though antiplatelet agent and statin are cornerstones for treating IHD, however, previous clinical studies showed that statin and aspirin was effective in decreasing VEGF levels and have no effects on promoting angiogenesis (Dworacka et al, 2014;Cheng et al, 2015). Recently, animal studies showed that VEFG for therapeutic angiogenesis could promotes collateral circulation in mouse heart by recruiting endothelial progenitor cells, and subsequently rescue myocardial tissue after an ischemic insult (Mallick et al, 2022). Transforming growth factor beta (TGF-β1) induces pro-reparative phenotypic changes in epicardial cells in mice after myocardial infarction (Dergilev et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Even though antiplatelet agent and statin are cornerstones for treating IHD, however, previous clinical studies showed that statin and aspirin was effective in decreasing VEGF levels and have no effects on promoting angiogenesis (Dworacka et al, 2014;Cheng et al, 2015). Recently, animal studies showed that VEFG for therapeutic angiogenesis could promotes collateral circulation in mouse heart by recruiting endothelial progenitor cells, and subsequently rescue myocardial tissue after an ischemic insult (Mallick et al, 2022). Transforming growth factor beta (TGF-β1) induces pro-reparative phenotypic changes in epicardial cells in mice after myocardial infarction (Dergilev et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The functions of VEGF-B are mediated by its binding to a tyrosine kinase receptor, named as vascular endothelial growth factor receptor 1 (VEGF-R1) and common co-receptors neuropilin 1 (NRP-1) or NRP-2 [ 27 , 28 , 29 ]. It needs to be pointed out that VEGF-B186 binds to VEGF-R1 before and after proteolytic cleavage but requires proteolytic cleavage to bind to NRP-1 or NRP-2 [ 28 , 30 ].…”
Section: Vascular Endothelial Growth Factor Bmentioning
confidence: 99%
“…The functions of VEGF-B are mediated by its binding to a tyrosine kinase receptor, named as vascular endothelial growth factor receptor 1 (VEGF-R1) and common co-receptors neuropilin 1 (NRP-1) or NRP-2 [ 27 , 28 , 29 ]. It needs to be pointed out that VEGF-B186 binds to VEGF-R1 before and after proteolytic cleavage but requires proteolytic cleavage to bind to NRP-1 or NRP-2 [ 28 , 30 ]. VEGF-A does not seem to significantly activate VEGF-R1 downstream signaling compared with VEGF-R2 mediated downstream signaling, while VEGF-B binding to VEGF-R1 leads to the activation of AKT, PI3K, ERK, and MAPK [ 31 ].…”
Section: Vascular Endothelial Growth Factor Bmentioning
confidence: 99%
See 2 more Smart Citations